A program for electronic medical education in Colombia, educacion electronica estructurada (E3): a succesful experience (2004)
Medical education in Colombia remains, almost completely, with the physical presence of the lecturer in the classroom. In recent years, new alternatives in higher education have been explored, on a balanced basis. Our faculty traditionally remains teaching with conservative methods; therefore, strategies for incorporating informatics, virtual education and in general, electronics are vital in our academic environment. Our electronic medical education group, E3, is constituted by faculty, undergraduate and graduate students. E3 was designed to provide the urgent need to develop an appropriate scenario for a group of faculty and students who will provide the school with clear cut policies and strategies, to establish a permanent and dynamic program of ICT locally, institutionally and regionally. The project, enveloped in the objectives of E3 includes: Electronic Academic Contents (EAC), Virtual Education Project (VEP) and Electronic Clinical Record (ECR). We will improve and increase, by the end of 2003, electronic medical education at our School and radiate to the University and the academic community.